Pengaruh Work-Life Balance terhadap Kesejahteraan Karyawan di Era Kerja Hybrid - Anna Chofyfa; Nadiah Faradhilla; Maiza Fikri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This paper investigates the relationship between work-life balance and employee well-being within the contemporary hybrid work environment through a systematic literature review approach. Findings indicate that while flexible working arrangements offer substantial autonomy and reduce commuting fatigue, they simultaneously introduce risks of digital burnout if institutional boundaries remain ambiguous. The analytical synthesis reveals that supportive leadership and robust organizational policies serve as critical mediating mechanisms to mitigate professional stress and enhance job satisfaction. Ultimately, achieving sustainable corporate performance in the modern digital era requires a paradigm shift toward outcome-oriented management that prioritizes human well-being alongside operational efficiency.